Mohamed Tharuwat Ismail Bakti : meneroka seni, berbakti kepada seni - Zainun Ishak (Petaling Jaya, Selangor : ZIT Publishing, 2012)
Biography of Mohamed Tharuwat Ismail Bakti, a Malaysian dancer, choreographer, and actor.
Includes musical scores with staff notation.
Includes bibliographical references (page 196).
In Malay.
Keywords: Mohamed Tharuwat Ismail Bakti, -- 1944-; Dancers -- Malaysia -- Biography; Choreographers -- Malaysia -- Biography; Actors -- Malaysia -- Biography; Artists -- Malaysia -- Biography